Age-Related Performance in Using a Fully Immersive and Automated Virtual Reality System to Assess Cognitive Function - Tan, Ngiap Chuan; Lim, Jie En; Allen, John Carson; Wong, Wei Teen; Quah, Joanne Hui Min; Muthulakshmi, Paulpandi; Teh, Tuan Ann; Lim, Soon Huat; Malhotra, Rahul (Frontiers in Psychology, 2022)
Introduction: Cognition generally declines gradually over time due to progressive degeneration of the brain, leading to dementia and eventual loss of independent functions. The rate of regression varies among the six cognitive domains (perceptual motor, executive function, complex attention, learning and memory, social cognition and language). Current modality of cognitive assessment using neuropsychological paper-and-pencil screening tools for cognitive impairment such as the Montreal Cognitive Assessment (MoCA) has limitations and is influenced by age. Virtual reality (VR) is considered as a potential alternative tool to assess cognition. A novel, fully-immersive automated VR system (CAVIRE) has been developed to assess the six cognitive domains. As cognition is associated with age, VR performance is postulated to vary with age using this system. Aims: This is a feasibility study to evaluate the VR performance of cognitively-healthy adults aged between 35-74 years old, based on the performance score and completion time using the CAVIRE system. Methods: Conducted in a public primary care clinic in Singapore, 25 multi-ethnic Asian adults were recruited in each of the four age groups in years: 1. 35-44; 2. 45-54; 3. 55-64 and 4. 65-74. The eligibility criteria included a MoCA score of 26 or higher to reflect normal cognition and understanding English instructions. They completed common daily activities ranging from brushing teething to shopping, across 13 VR segments. Their performances scores and completion time were automatically computed by the CAVIRE system. These VR performance indices were compared across the four age groups using one-way ANOVA, F-test of the hypothesis, followed by pair-wise comparisons in the event of a significant F-test (p<0.05). Results: One participant dropped out from Group 1. The demographic characteristics of 99 participants were similar across the 4 age groups. Overall, younger participants in Groups 1 and 2 attained higher VR performance scores and shorter completion time, compared to those in Groups 3 and 4, in all six cognitive domains (all p<0.05). Conclusion: The CAVIRE VR performance scores and completion time significantly differ between the younger and older Asian participants with normal cognition. Enhancements to the system are needed to establish the age-group specific normal performance indices.